2017
DOI: 10.1039/c7ta01791j
|View full text |Cite
|
Sign up to set email alerts
|

Fe2P/reduced graphene oxide/Fe2P sandwich-structured nanowall arrays: a high-performance non-noble-metal electrocatalyst for hydrogen evolution

Abstract: Vertical sandwich-like architectures of Fe2P@rGO were constructed and performed well in terms of excellent HER activity and high stability simultaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(70 citation statements)
references
References 46 publications
0
70
0
Order By: Relevance
“…Among these materials, transition metal phosphides (TMPs) such as MoP 2 , WP 2 , FeP 2 , FeP, Ni 2 P, CoP, and so on, have received growing attention as promising HER electrocatalysts because of their intrinsic catalytic property, high electrochemical stability and low cost. Nonetheless, the electrocatalytic performances of TMPs‐based materials cannot fully meet the requirement of practical applications, due to the relatively slow charge transportation and lack of exposed active sites .…”
Section: Introductionmentioning
confidence: 99%
“…Among these materials, transition metal phosphides (TMPs) such as MoP 2 , WP 2 , FeP 2 , FeP, Ni 2 P, CoP, and so on, have received growing attention as promising HER electrocatalysts because of their intrinsic catalytic property, high electrochemical stability and low cost. Nonetheless, the electrocatalytic performances of TMPs‐based materials cannot fully meet the requirement of practical applications, due to the relatively slow charge transportation and lack of exposed active sites .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the specific activity estimated from the normalization of LSV curve with ESA shown in Figure S7 also suggested that Fe@Fe 2 P/ NCNT exhibited higher intrinsic activity compared to Fe/NCNT electrocatalyst. [30] Meanwhile, Fe@Fe 2 P/NCNT electrocatalyst exhibited considerably high HER activity compared to Fe 2 P/RGO/Fe 2 P (101 mV), [23] Fe 2 P/GCS (88 mV) [26c] and Fe 2 P/GC (76 mV) [31] electrocatalysts. [28] NCNT and Fe@Fe 2 O 3 /NCNT with Tafel slopes of 179.1 mV dec À 1 and 151 mV dec À 1 manifested the sluggish HER kinetics due the few active sites for HER.…”
Section: Resultsmentioning
confidence: 99%
“…The GR-Ni foam had a smaller semicircle diameter than bare Ni foam, indicating that the introduction of GR increased conductivity and promoted electron transfer [32,33]. Additionally, cyclic voltammetry (CV) can determine the double layer capacitance (Cdl) which is linearly proportional to effective active surface area [34,35]. The CV current responses for the Ni foam and GR-Ni foam electrodes in the region from -0.15 to -0.05 V vs. SCE should be mostly due to the charging of the double layer ( Figure S1a and b).…”
Section: Characterizationsmentioning
confidence: 99%